2015
DOI: 10.1109/twc.2015.2432755
|View full text |Cite
|
Sign up to set email alerts
|

Channel Measurements and Modeling for a 60 GHz Wireless Link Within a Metal Cabinet

Abstract: Abstract-This paper presents the channel measurements performed within a closed metal cabinet at 60 GHz covering the frequency range 57-62 GHz. Two different volumes of an empty metal cupboard are considered to emulate the environment of interest (an industrial machine). Furthermore, we have considered a number of scenarios such as line of sight, non line of sight, and placing absorbers. A statistical channel model is provided to aid short-range wireless link design within such a reflective and confined enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Radio propagation measurements at the sub-THz band in indoor industrial environments are expected to attract more research interest [ 40 ]. For instance, a few mmWave radio propagation measurements have been conducted in various industrial environments at 28 GHz [ 44 , 45 , 46 , 47 , 48 , 49 , 50 ] and 60 GHz [ 44 , 51 , 52 ]. Narrowband measurements were conducted inside a factory environment at 28 GHz in [ 46 ] to study the path loss at a 5–100 m distance over 400 LoS and NLoS measured points, and it was shown that the PLE values were 2 and 4.1 for LoS and NLoS, respectively.…”
Section: Overview Of Radio Propagation Measurements In Industrial mentioning
confidence: 99%
“…Radio propagation measurements at the sub-THz band in indoor industrial environments are expected to attract more research interest [ 40 ]. For instance, a few mmWave radio propagation measurements have been conducted in various industrial environments at 28 GHz [ 44 , 45 , 46 , 47 , 48 , 49 , 50 ] and 60 GHz [ 44 , 51 , 52 ]. Narrowband measurements were conducted inside a factory environment at 28 GHz in [ 46 ] to study the path loss at a 5–100 m distance over 400 LoS and NLoS measured points, and it was shown that the PLE values were 2 and 4.1 for LoS and NLoS, respectively.…”
Section: Overview Of Radio Propagation Measurements In Industrial mentioning
confidence: 99%
“…It is worth noting that the environment description given above is amenable to other similar scenarios such as embedded systems for intelligent metasurfaces [35], but not generalizable to all wireless scenarios within computing systems. For instance, several works have proposed models for the mmWave wireless channel within a rack [36], between racks [37]- [39] or at the cabinet scale [40] in data centers. Some papers have also covered the channel at the motherboard scale in desktops or laptops [8], [41]- [49].…”
Section: B Environment Descriptionmentioning
confidence: 99%
“…Others simply assume free space over the insulator layer [18], [31]- [34]. To find similar results, we need to refer to works at the data center cabinet scale [46], or at the motherboard scale in desktops or laptops [19], [47], [48], which have structural resemblances. However, their results are not directly applicable to the chip scale due to substantial differences in dimensions, materials, and antenna placement restrictions.…”
Section: Introductionmentioning
confidence: 99%